Influence of the transient airflow pattern on the temporal evolution of microparticle resuspension: Application to ventilated duct during fan acceleration. Issue 11 (29th September 2022) - Theron, Félicie; Debba, Djihad; Le Coq, Laurence
Abstract: This study investigates experimentally the influence of the temporal airflow pattern properties to which microparticles are exposed on the dynamics of the resuspension phenomenon for transient airflow conditions representative of a fan start, i.e., involving a temporal acceleration period before reaching steady state. The extent to which the average steady state velocity and the average acceleration affect the characteristics of the curve depicting the temporal evolution of the fraction of particles remaining on the duct wall, i.e., the time at which resuspension starts and the curve shape, is investigated. These results are analyzed regarding the properties of the instantaneous velocity signal in the viscous sublayer. It is demonstrated that a threshold turbulent kinetic energy must be exceeded for resuspension to begin. The results are also presented in terms of resuspension rate, i.e., of instantaneous rate of particles removed from the duct surface, versus time. This enables to demonstrate that the highest resuspension rate values are recorded at the very beginning of the phenomenon, typically during the fan acceleration stage, and that high mean acceleration values are responsible for high resuspension rates. Copyright © 2022 American Association for Aerosol Research